Occurrence of endoparasites in wild Antillean manatees (Trichechus manatus manatus) in Colombia. Issue 1 (April 2018) - Vélez, J.; Hirzmann, J.; Lange, M.K.; Chaparro-Gutiérrez, J.J.; Taubert, A.; Hermosilla, C.
Abstract: The recognized impact of parasites in wildlife populations demands surveillance of endangered species like the Antillean manatees ( Trichechus manatus manatus ) in Colombia. We conducted a parasitological survey in four rescued sea cows in order to document the parasite diversity of this sirenian in the Caribbean wetland of Colombia and contribute to the molecular characterization of its trematodes. The flukes Chiorchis fabaceus, Nudacotyle undicola and the protozoans Eimeria manatus and E. nodulosa were identified in analysed faecal samples. For C. fabaceus and N. undicola, partial regions of ribosomal RNA genes were amplified and sequenced in order to infer their phylogenetic relations. The current study constitutes a new sirenian host ( T. manatus manatus ) record for the genus Eimeria and the trematode N . undicola . Graphical abstract: Image 1 Highlights: Gastrointestinal parasites of the Antillean manatee of Caribbean wetland in Colombia. First report of Eimeria species and N. undicola in the Antillean manatee ( T. manatus manatus ). First contribution to the phylogenetic knowledge of trematode parasites of manatees.